Brute necessity. Issue 9 (12th July 2018) - Van Cleve, James
Abstract: In a growing number of papers, one encounters arguments to the effect that certain philosophical views are objectionable because they would imply that there are necessary truths for whose necessity there is no explanation. That is, they imply that there are propositions p such that (a) it is necessary that p, but (b) there is no explanation why it is necessary that p. For short, they imply that there are "brute necessities." Therefore, the arguments conclude, the views in question should be rejected in favor of rival views under which the necessities would be explained. This style of argument raises a number of important and difficult questions. Do necessary truths really require explanation? Are they not paradigms of truths that either need no explanation or automatically have one, being in some sense self‐explanatory? If some necessary truths do require or admit of explanation, what types of explanation, are available? Are some necessary truths explained by other necessary truths? Are some necessary truths self‐explanatory? Are all necessary truths either self‐explanatory or explained by others? Or are there some necessary truths that are truly brute? This article surveys several representative arguments from brute necessity as well as a variety of answers to the questions above, noting their bearing on arguments from bruteness.